SAT0416 Life-threatening primary sjÖgren syndrome: clinical characterisation and outcomes in 1535 patients (GEAS-SS REGISTRY). (12th June 2018) - Retamozo, S.; Flores-Chávez, A.; Kostov, B.; Solans, R.; Fraile, G.; Maure, B.; Feijoo, C.; Rascón, F.J.; Pérez-Alvarez, R.; Zamora, M.; García-Pérez, A.; Lopez-Dupla, M.; et al.
Abstract : Objectives: To analyse the clinical features and outcomes of patients presenting with life-threatening systemic disease in a large cohort of Spanish patients with primary Sjogren syndrome (SjS). Methods: The GEAS-SS multicenter registry was formed in 2005 with the aim of collecting a large series of Spanish patients with primary SS. By January 2018, the database included 1535 consecutive patients fulfilling the 2002/2016 criteria. Life-threatening systemic disease was defined as an activity level scored as "High" in at least one ESSDAI domain. Results: 209 (14%) were classified as presenting with a life-threatening systemic disease: 194 presented one ESSDAI domain classified as high, 14 two domains and only one presented three high activity domains. The high-ESSDAI domains included lymphadenopathy in 78 (37%) cases, CNS in 28 (13%), PNS in 25 (12%), pulmonary in 25 (12%), renal in 22 (10%), cutaneous in 18 (9%), articular in 18 (9%), haematological in 7 (3%) and muscular in 4 (2%); the most frequent clinical presentations in each domain were, respectively, parotid lymphoma (n=41), focal neurological deficit (n=20), ganglionopathy (n=11), usual interstitial pneumonitis (n=9), renal failure (n=11), ulcerated cutaneous vasculitis (n=9), symmetric polyarthritis (m=17), severe thrombocytopenia (n=3) and severe myositis (n=3). With respect to therapeutic approach, 144 (69%) required glucocorticoids, 65 (31%) immunosuppressive agents and 42 (20%) biological therapies. During the follow-up, 36 (17%) patients died, mainly due to lymphoma (n=16), pulmonary fibrosis (n=5), end-stage renal failure (n=4), CNS progressive disease (n=3) and systemic vasculitis (n=3). Conclusions: A 14% of patients with primary SjS develop a potentially life-threatening systemic disease (mainly lymphoma, but also severe internal organ involvements including nervous system, the lungs and the kidneys). This subset of patients requires intensive therapeutic management with a mortality rate of nearly 20% of cases. Disclosure of Interest: None declared